Analisis Penerimaan Teknologi Mobile Banking Terhadap Use Behavior Melalui Pendekatan Model Utaut 2 (Studi Pada Nasabah KCU BCA Malang) - Wira Bharata; Premi Wahyu Widyaningrum (UNIVERSITAS PGRI MADIUN, 2020)
The development of internet technology is also adopted by state and private banks to develop services. Internet banking is a revolutionary and strategic weapon for bank operations, product delivery, and to face competition between banks. The security and convenience of conducting transactions is a key driver for mobile banking growth. The presence of smartphones supports more types of online banking services. This study was conducted to predict the acceptance and adoption of information technology, especially mobile banking to bank customers. The approach of this research is quantitative research approach. The type of research used is survey research. Samples were taken using simple random sampling. The sample size was determined by 53 people, using the Machin and Chambel formula. The population in this research is KCU BCA Malang customer. Empirical data were collected through survey methodology. The data will be analyzed through the Generalized Structured Component Analysis (GSCA). Research findings indicate that there are positive outcomes of all relationships measured.Keywords: UTAUT, Mobile Banking, Behavioral Intention, Use Behavior.